Hubungan Antara Self Control dan Social Interaction Terhadap Perilaku Sosial Mahasiswa Jurusan Pendidikan Fisika Fakultas Tarbiyah dan Keguruan Uin Alauddin Makassar - Jusman, Jusman; Hajeriati, Hajeriati; Hijria.A, Hijria.A (UIN Alauddin Makassar, 2021)
The research aims to describe and interpret the relationship between Self Control and Social Interaction with the Social Behavior of Physics Education Students. The research was conducted at the Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar. Research variables are Self Control and Social Interactionand StudentSocial Behavior. The study population was the class of 2009, 2010, 2011 and 2012. The sampling technique used was proportional stratified random sampling technique. Sampling based on levels is taken randomly. The instruments used were questionnaires and documentation with descriptive statistical data analysis techniques and inferential statistics for hypothesis testing. The results showed that the descriptive analysis showed that the average score of Self Control was 90.95 and the average score of Social Interaction was 94.12, each score was in the sufficient category. And the average score of Student Social Behavior is 106.98 which is in the sufficient category. Inferential analysis shows the value of Fcount = 1574.65 while Ftable at the 5% significance level is 3.18. Thus, the value of Fcount is greater than the value of Ftable, so H0 is rejected, meaning that there is a significant relationship between Self Control and Social Interaction with the Social Behavior of Students of the Department of Physical Education at UIN Alauddin Makassar.